Wealth Concentration and Pandemic: A Simple Model of Economic Activity - Ortiz Quevedo, Carlos Humberto (Sociedad y Economía, 2023)
A general economic equilibrium/imbalance model is constructed to analyze the impacts of capital concentration. In this context, the conjunctural impact of a pandemic is analyzed. Results: 1) Capitalism requires the original accumulation of capital; 2) The concentration of capital increases the working population, decreases wages, increases profits and decreases economic activity; 3) From a threshold of capital concentration, the wage can no longer decrease and/or loses the ability to balance the system, labor unemployment appears and a minimum wage is imposed; 4) There is an optimal minimum wage (minimizes unemployment); 5) Higher agricultural productivity decreases unemployment and increases output; 6) An optimal basic income for workers and a subsistence bonus for the inactive reestablishes general economic equilibrium; 7) Capital concentration requires progressive taxation; 8) The model replicates some impacts of the pandemic and social explosion on economic activity in Colombia.